A Dictionary of the Malay Tongue : In Two Parts, to Which Is Prefixed a Grammar of that Language - Howison, James (Place of publication not identified : publisher not identified, 1801)
Published in 1801, this work is largely based on the first Malay-English dictionary, published 100 years earlier by Thomas Bowrey. A member of the Asiatic Society, although not recognised as a Malay scholar, James Howison seems to have lent his name to this version, produced in order to fill the gap caused by the scarcity of copies of the earlier dictionary. Since the British East India Company established a presence in the Malay Peninsula in 1786, the need for a compendium of working Malay had greatly increased. This reissue brings together the two parts of the dictionary in one volume for bidirectional coverage, and it includes the transliteration, though flawed, of the Arabic script of Jawi. Although superseded by William Marsden's 1812 dictionary and grammar (also reissued in this series), this nevertheless remains an interesting historical document, offering insight into the early colonial study of a language.
Title from publisher's bibliographic system (viewed on 07 Mar 2017).